2002
DOI: 10.3310/hta6040
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of discharge arrangements for older people

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
157
0
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(170 citation statements)
references
References 117 publications
(466 reference statements)
3
157
0
8
Order By: Relevance
“…Data regarding the effectiveness of pre-and postdischarge interventions have been mixed, but targeting these lower acuity admissions may be more cost-effective than interventions addressing long-term outpatient disease management. [38][39][40][41][42][43][44][45] Primary care access and ED utilization patterns have been examined in multiple studies looking at risk for admission, with varying results. 4,6,12,13,[46][47][48] In our study, self-reported ambulatory care did not differ between the patients with strongly acuity-driven and moderately/weakly acuity-driven admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the effectiveness of pre-and postdischarge interventions have been mixed, but targeting these lower acuity admissions may be more cost-effective than interventions addressing long-term outpatient disease management. [38][39][40][41][42][43][44][45] Primary care access and ED utilization patterns have been examined in multiple studies looking at risk for admission, with varying results. 4,6,12,13,[46][47][48] In our study, self-reported ambulatory care did not differ between the patients with strongly acuity-driven and moderately/weakly acuity-driven admissions.…”
Section: Discussionmentioning
confidence: 99%
“…61 In a recent metareview, Mistiaen and colleagues 24 retrieved systematic reviews published between 1994 and 2004 that assessed effectiveness of peridischarge interventions aimed at reducing postdischarge problems in adults discharged home from acute general hospital care. Of 15 reviews selected, only three showed reductions in readmissions and all three 22,54,62 were characterised by the combination of patient education and preand postdischarge support.…”
Section: Studies Of Integrated Pre-and Postdischarge Multicomponent Imentioning
confidence: 99%
“…26 These include the Hospital Admission Risk Profile, Identification of Seniors at Risk, and Care Complexity Prediction Instrument. In three reviews, 22,23,27 systematic use of these instruments exerted no significant effects on readmission rates.…”
Section: Screening Of Individuals At High Risk Of Discharge Failurementioning
confidence: 99%
See 1 more Smart Citation
“…2,3 We read with interest Woodard and Conroy's description of an acute frailty unit, which will likely improve the standard of care provided to older patients, and we await with further data from their experience.…”
Section: In Response -Additional Support To High-risk Patients Can Rementioning
confidence: 99%